Psychological outcomes of the COVID-19 pandemic among pregnant women in Indonesia: a cross-sectional study - Rahmah Hida Nurrizka (Korea Centers for Disease Control & Prevention, 2021)
Objectives The objective of this study was to analyze the psychological outcomes of pregnant women during the coronavirus disease 2019 (COVID-19) pandemic in several areas that are epicenters for the spread of the severe acute respiratory syndrome coronavirus 2 in Indonesia. Methods This cross-sectional study used data obtained from an online survey administered to 120 women who were pregnant and gave birth during the COVID-19 pandemic in Indonesia. The psychological condition of pregnant women was measured using the Depression, Anxiety, and Stress Scale-21 questionnaire which was modified for conditions experienced during the COVID-19 pandemic. We classified pregnant women into 2 groups according to their psychological condition: pregnant women who experienced anxiety and pregnant women who did not experience anxiety or felt normal. Receiver operating characteristic (ROC) analysis was undertaken for the 2 groups. This study also used univariate analysis and bivariate analysis. Results The results of the ROC analysis resulted in a cutoff score of 3.56. The proportion of respondents who felt anxious was 53.3% and the proportion of respondents who did not feel anxious or felt normal was 46.7%. Anxiety was most common among pregnant women with high education levels, gestational age <19 weeks, and working pregnant women. Conclusion Maternal health services need to be performed with strict health protocols, complemented by pregnancy counseling services. This will provide a feeling of comfort and safety as pregnant women receive health services and give birth.